(untitled) (International Journal of Built Environment and Sustainability, 2022)
Nowadays, there exists a high incidence of competitions between organizations seeking control, relevance, and dominance in the market space due to globalization exacerbated by the continuous advancement in technologies, high customers’ tastes, and expectations. This has significantly influenced organizational decisions leading to constant reevaluation of operational procedures, adopting and implementing changes that will influence positive business outcomes. The literature search revealed that past studies on organizational leadership focused mainly on elements of leadership styles, strategies, and ethics. Hence, studies have not identified the factors that influence organizational leadership for adequate housing delivery in Nigeria. The study identified the factors that influence organizational leadership in the delivery of housing in Nigeria using the Broaden and Build theory, and Kurt Lewin’s leadership philosophical concepts as the fundamental basis underpinning the study. Delphi study approach was used to determine the areas of commonality before a consensus was reached. A structured questionnaire was administered to validate and removing outliers from the result. The Delphi study identified 20 distinct factors that influence organizational leadership for AHD in Nigeria. Factors such as organizational sustainability, motivation, etc., are the most significant factors influencing organizational leadership towards AHD. However, results from SEM analysis showed that only 12 variables are significant in measuring organizational leadership and management for AHD. The study concludes that the 12 identified factors are significant in AHD. Nevertheless, the application of these factors in housing delivery is still low in Nigeria. Hence, it is recommended that real estate developers and other operators in housing should use the result from this study as a template for developing adequate housing.